Composition of Trace Metals in Dust Samples Collected from Selected High Schools in Pretoria, South Africa - J. O. Olowoyo; L. L. Mugivhisa; Z. G. Magoloi (Applied and Environmental Soil Science)
Potential health risks associated with trace metal pollution have necessitated the importance of monitoring their levels in the environment. The present study investigated the concentrations and compositions of trace metals in dust samples collected from classrooms and playing ground from the selected high schools In Pretoria. Schools were selected from Pretoria based on factors such as proximity to high traffic ways, industrial areas, and residential areas. Thirty-two dust samples were collected from inside and outside the classrooms, where learners often stay during recess period. The dust samples were analysed for trace metal concentrations using Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). The composition of the elements showed that the concentrations of Zn were more than all other elements except from one of the schools. There were significant differences in the concentrations of trace metals from the schools (p<0.05). Regular cleaning, proximity to busy road, and well maintained gardens seem to have positive effects on the concentrations of trace metals recorded from the classrooms dust. The result further revealed a positive correlation for elements such as Pb, Cu, Zn, Mn, and Sb, indicating that the dust might have a common source.